Epidemiology of Haemophilia in Greece: An Overview - Koumbarelis, Emmanuil; Rosendaal, Frits R; Gialeraki, Argyri; Karafoulidou, Anastasia; Noteboom, Willy M P; Loizou, Calliopi; Panayotopoulou, Catherine; Markakis, Constantine; Mandalaki, Titica (Thrombosis and Haemostasis, 1994)
Demographic data of the Greek haemophilia A and B population for the period 1972-1993 were analyzed. Prevalence at birth including known not-registered patients was calculated at 23.1 per 100,000 male births. However, the observed prevalence in 1993 was only 61% of the expected. Since 1975 the proportion of mild cases had significantly increased. Adjusted by age, severity and HIV status reproductive fitness of haemophiliacs was 0.62. Overall mortality was 2.6 times higher than in the general population, but 7.9 times among patients with severe haemophilia and 16.4 among HIV(+) haemophiliacs. Fifty out of 78 deaths occurred among HIV(+) patients and 28 of these were caused by AIDS. Inhibitor patients did not show excess mortality due to bleeding. Cancer mortality was equal to normal, but the number of deaths from ischaemic heart disease was 0.25 of the expected. Risk of death due to cerebral haemorrhage was 3.8 times higher in HIV(+) haemophiliacs than in HIV(-).